Evaluasi Pembelajaran BIPA di Kelas BIPA 3 KBRI Moscow - Raden Yusuf Sidiq Budiawan (Universitas PGRI Semarang, 2023)
The purpose of this research is to study how the Indonesian Language for Speakers of Other Languages (BIPA) learning program in BIPA 3 class at the Indonesian Embassy in Moscow works, how learners respond to the lessons, and how the evaluation impacts improving the understanding and language skills of non-native learners. Involving seven BIPA learners in the BIPA 3 class at the Indonesian Embassy in Moscow, a descriptive-qualitative method was used. Data were collected through documentation, interviews, and observation. The triangulation method was used to gain a complete understanding of learning evaluation. The results show that BIPA 3 learners at the Indonesian Embassy in Moscow are very interested in learning Indonesian. They show progress in reading, writing, listening, and speaking. However, learners develop differently, and some need to improve their skills in some areas. Overall, the learning evaluation of BIPA in the BIPA 3 class at the Indonesian Embassy in Moscow has an important role in improving learners' language understanding and skills and helping to develop more effective learning programs.ABSTRAKTujuan penelitian ini adalah untuk mempelajari bagaimana program pembelajaran Bahasa Indonesia bagi Penutur Asing (BIPA) di kelas BIPA 3 KBRI Moscow, bagaimana pemelajar menanggapi pelajaran, dan bagaimana evaluasi berdampak pada peningkatan pemahaman dan keterampilan berbahasa bagi pemelajar non-natif. Melibatkan tujuh pemelajar BIPA yang berada di kelas BIPA 3 di KBRI Moscow, metode deskriptif kualitatif digunakan. Data dikumpulkan melalui dokumentasi, wawancara, dan observasi. Metode triangulasi digunakan untuk mendapatkan pemahaman yang lengkap tentang evaluasi pembelajaran. Hasil penelitian menunjukkan bahwa pemelajar BIPA 3 di KBRI Moscow sangat tertarik untuk belajar bahasa Indonesia. Mereka menunjukkan kemajuan dalam membaca, menulis, menyimak, dan berbicara. Namun, pemelajar berkembang secara berbeda, dan beberapa perlu meningkatkan keterampilan mereka dalam beberapa area. Secara keseluruhan, evaluasi pembelajaran BIPA di kelas BIPA 3 KBRI Moscow memiliki peran penting dalam meningkatkan pemahaman dan keterampilan berbahasa pembelajar dan membantu mengembangkan program pembelajaran yang lebih efektif.